Production of d-Branched-Chain Amino Acids by Lactic Acid Bacteria Carrying Homologs to Isoleucine 2-Epimerase of Lactobacillus buchneri - Mutaguchi, Yuta; Kasuga, Kano; Kojima, Ikuo (Frontiers in Microbiology, 2018)
Isoleucine 2-epimerase (ILEP) is a novel branched-chain amino acid racemase isolated from Lactobacillus buchneri. In this study, we examined production of free D-branched-chain amino acids such as D-valine, D-leucine, and D-allo-isoleucine, using lactic acid bacteria carrying homologs to ILEP. Twelve selected strains of lactic acid bacteria were grown at optimal growth temperatures and accumulation of D-branched-chain amino acids in the medium was monitored in exponential, early stationary, and stationary phases. To analyze the D-branched-chain amino acids, enantiomers in the medium were initially converted into diastereomers using pre-column derivatization with o-phthaldialdehyde plus N-isobutyryl-L-cysteine. The resultant fluorescent isoindole derivatives were analyzed on an octadecylsilyl stationary phase using ultra-high performance liquid chromatography. The analyses revealed that the seven following lactic acid bacteria carrying homologs showing 53– 60% amino acid sequence identity to the L. buchneri ILEP accumulate D-branched-chain amino acids: Lactobacillus fermentum and Weissella paramesenteroides produce D-valine, D-leucine, and D-allo-isoleucine; Lactobacillus reuteri, Leuconostoc mesenteroides subsp. mesenteroides, and Leuconostoc gelidum subsp. gasicomitatum accumulate D-leucine and D-allo-isoleucine; and Lactobacillus vaginalis and Leuconostoc pseudomesenteroides produce D-allo-isoleucine. These results suggest that D-branched-chain amino acids are produced by a variety of lactic acid bacteria species, particularly those carrying homologs to the ILEP.